Application of CuxO-FeyOz Nanocatalysts in Ethynylation of Formaldehyde - Haitao Li (Nanomaterials, 2019)
Composite nanomaterials have been widely used in catalysis because of their attractive properties and various functions. Among them, the preparation of composite nanomaterials by redox has attracted much attention. In this work, pure Cu2O was prepared by liquid phase reduction with Cu(NO3)2 as the copper source, NaOH as a precipitator, and sodium ascorbate as the reductant. With Fe(NO3)3 as the iron source and solid-state phase reaction between Fe3+ and Cu2O, CuxO-FeyOz nanocatalysts with different Fe/Cu ratios were prepared. The effects of the Fe/Cu ratio on the structure of CuxO-FeyOz nanocatalysts were studied by means of X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), ultraviolet confocal Raman (Raman), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS, XAES), and hydrogen temperature-programmed reduction (H2-TPR). Furthermore, the structure−activity relationship between the structure of CuxO-FeyOz nanocatalysts and the performance of formaldehyde ethynylation was discussed. The results show that Fe3+ deposited preferentially on the edges and corners of the Cu2O surface, and a redox reaction between Fe3+ and Cu+ occurred, forming CuxO-FeyOz nanoparticles containing Cu+, Cu2+, Fe2+, and Fe3+. With the increase of the Fe/Cu ratio, the content of CuxO-FeyOz increased. When the Fe/Cu ratio reached 0.8, a core−shell structure with Cu2O inside and a CuxO-FeyOz coating on the outside was formed. Because of the large physical surface area and the heterogeneous structure formed by CuxO-FeyOz, the formation of nonactive Cu metal is inhibited, and the most active species of Cu+ are exposed on the surface, showing the best formaldehyde ethynylation activity.